Theoretical Basis of Working on Course Tasks in Higher Philogical Education - Khazratqulova Ozoda Abduganiyevna (International Journal on Integrated Education, 2026)
In philology, we understand useful knowledge as knowledge that serves to form students' skills in literate writing, creative thinking, and correct and fluent expression in oral and written forms in accordance with the conditions of speech, and that ensures their upbringing and development in the spirit of high human virtues. In this regard, learning tasks are considered an important factor in revealing the content of the lesson. The most important indicator of the quality of education and the means involved in the formative and testing process are the system of exercises, as well as questions and assignments. They form the content of language learning and the basis of teaching methodology.